2019
DOI: 10.1039/c9bm00991d
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine/puerarin nanoparticle-incorporated hybrid hydrogels for enhanced wound healing

Abstract: Oxidative damage generated would disrupt the oxidant/antioxidant balance in cells, causing slow wound healing and tissue regeneration. Hydrogel dressing with antioxidant properties can promote wound healing, however, its design is still a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…The wound healing process was monitored by an optical microscope and a confocal microscope for up to two weeks. [ 54 ]…”
Section: Methodsmentioning
confidence: 99%
“…The wound healing process was monitored by an optical microscope and a confocal microscope for up to two weeks. [ 54 ]…”
Section: Methodsmentioning
confidence: 99%
“…The administration of FA reduces oxidative stress and DNA damage caused by lead acetate [ 42 ]. In our previous study, we showed that the hydrogel incorporated with PUE exerted excellent antioxidant effects, which promoted the regeneration and healing of damaged skin [ 43 ]. In the present study, we found that PUE and FA have a synergistic role in resisting oxidative stress damage in vitro and promoting wound healing in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…In Figure S1a (Supporting Information), the MICH matrix exhibited extremely rapid water absorption capacity within the first 100 min and yielded a swelling saturation ratio of up to 2269%, implying that the MICH may quickly absorb tissue exudate and leaked blood when it applied to wound beds. [ 31 ] Generally, high molecular weight (MW) hyaluronan (HA) plays a significant biological activity in the tissue microenvironment, while low MW‐HA causes inflammation and tissue fibrosis. [ 32 ] In Figure S1b (Supporting Information), the degradation ratio of MICH showed relatively stable trends within 10 days, indicating the MICH matrix may maintain the structural integrity of high MW‐HA in PBS, facilitating the anti‐inflammatory effects of HA on wound tissue.…”
Section: Resultsmentioning
confidence: 99%